Whole-pattern profile fitting of powder diffraction data collected in parallel-beam flat-plate asymmetric reflection geometry - Rowles, Matthew; Madsen, I. (IUCr Journals, 2010)
Abstract: A simple, physically based model that allows the whole-pattern profile fitting of diffraction data collected in parallel-beam flat-plate asymmetric reflection geometry is presented. In this arrangement, there is a fixed angle between the incident beam and the sample, resulting in a fixed-length beam footprint. The use of a wide-angle detector for the simultaneous detection of the data precludes the use of any diffracted beam optics. Therefore, the observed peak widths are a function of the length of the beam footprint on the sample. The model uses up to three refinable parameters, depending on the intensity profile of the beam, to calculate the effect of diffraction angle on the width of all diffracted peaks. The use of this model reduces the total number of parameters required to fit the observed peak widths and shapes, hence leading to increased stability in the profile analysis. Implementations of the model are provided for both fundamental parameters and empirical approaches.